Sistema de Gestión de la Calidad para el Proceso de Organización de la Universidad de Otavalo - Perachimba F., Tania E. (2017)
The project includes the design of a Quality Management System for the organizational process of the University of Otavalo, with the objective of establishing procedures and improving processes related to Institutional Ethics, Institutional Planning and Quality Management.